Application of Computers to the Teaching of Mining Engineering - L. Wade (The Southern African Institute of Mining and Metallurgy, 1987)
The advent of relatively cheap computing power has precipitated a rapid growth of computer usage in the mining industry. In order to obtain most benefit from this development a need is recognised for the future mining graduate to be trained in computer literacy. This paper outlines the type of training required and describes progress to date with such a programme at the University of the Witwatersrand. Certain challenges concerning the teaching effort are discussed.